2017
DOI: 10.1007/s11548-017-1585-6
|View full text |Cite
|
Sign up to set email alerts
|

Design, development and clinical validation of computer-aided surgical simulation system for streamlined orthognathic surgical planning

Abstract: Purpose There are many proven problems associated with traditional surgical planning methods for orthognathic surgery. To address these problems, we developed a computer-aided surgical simulation (CASS) system, the AnatomicAligner, to plan orthognathic surgery following our streamlined clinical protocol. Methods The system includes six modules: image segmentation and three-dimensional (3D) reconstruction, registration and reorientation of models to neutral head posture, 3D cephalometric analysis, virtual ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…Initial results have been promising. 22,23 Currently, we are collecting data to validate this algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Initial results have been promising. 22,23 Currently, we are collecting data to validate this algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The first medical fabrication laboratory in Japan was established at Tokyo Dental College—the “Fab Lab TDC”—in December 2013 [1]. Techniques to construct full-scale 3D models, such as of the jaw, based on computed tomography (CT) and magnetic resonance imaging (MRI) modalities have been reported recently [1–3]. We have also created preoperative 3D-printed models of cases for tumors in maxilla and mandible, jaw deformities, and used them primarily consultation to patients and for preoperative simulations.…”
Section: Introductionmentioning
confidence: 99%
“…However, while models created with a separate mandible and maxilla have good operability, it can be difficult to fully restore the position of the mandibular condyle after simulations. To fully restore the position of the condyle, methods have been reported that include the manufacture of a device to maintain the configuration of the mandible and embedding of magnets into the joint [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Multiple disciplines, such as cell biology, biomaterial research and biomedical engineering have contributed to the advances of tissue engineering technologies. Any tissue engineering approach is composed of three major components: (1) cells, (2) biocompatible scaffolds, and (3) suitable biochemical (e.g. growth factors) and physical (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of synthetic biodegradable polymers has been investigated as TE scaffold materials, though the main disadvantage of these materials is their lack of functional groups [2,3]. This results in limited capacity to combine with bioactive elements to reinforce their cell affinity [3].…”
Section: Introductionmentioning
confidence: 99%